SOSIALISASI PENTINGNYA MENJAGA KEAMANAN DATA PRIBADI DARI KEJAHATAN DI INTERNET - Muhammad Aulia Rizki (Abdi Jurnal Publikasi, 2023)
In this era of globalization, the development of the internet world has been very rapid. Especially among junior high school (SMP) students. It is undeniable that the internet is something that is often visited by students. What's more, they really like playing social media. According to them, playing social media can be a place to interact with other people. They can share all the information they have with others. On the one hand, sharing information on social media can lead to internet crimes. There are lots of crimes on the internet such as fraud, content containing religious elements, data theft and data misuse. One example that often occurs is the misuse of personal data. Misuse of this data occurs due to a lack of individual awareness regarding the protection of personal data, especially among junior high school students. Most students do not realize that the shared data can be misused by irresponsible parties. Therefore, there needs to be a sense of awareness about the importance of protecting personal data on the internet, especially for students of SMP Mabad Rempoa. So the purpose of holding this PKM is so that they can be careful in sharing information about themselves on the internet. Therefore, it is necessary to socialize students so that they can increase understanding in playing social media wisely. Keywords: Internet; Personal data; Social media; Internet crime;